Impact of intra-articular injection with tranexamic acid on total blood loss and postoperative pain after arthroscopic rotator cuff repair surgery - Zhu, Rangteng; Jiang, Hantao; Xu, Wei; Shen, Liping; Jin, Gang (Frontiers in Surgery, 2023)
Objectives: To evaluate the impact of intra-articular injection with tranexamic acid (TXA) on total blood loss (TBL) and postoperative pain after arthroscopic rotator cuff repair (ARCR). Methods: This study retrospectively included patients with full-thickness rotator cuff tears who underwent shoulder ARCR surgery in Taizhou hospital, China, between January 2018 and December 2020. Patients received 10 ml (100 mg/mL) of intra-articular TXA injection (TXA group) or 10 ml of normal saline (non-TXA group) after the incision was sutured. The primary variable was the type of drug injected into the shoulder joint at the end of the operation. The primary outcome were perioperative TBL and postoperative pain (measured by visual analog scale [VAS]). The secondary outcomes were differences in red blood cell count, hemoglobin count, hematocrit, platelet count. Results: A total of 162 patients were included, 83 patients in TXA group and 79 patients in non-TXA group. Notably, patients in TXA group were more likely to have lower TBL volume [261.21 (175.13-506.67) ml vs. 382.41 (236.11-593.31), P = 0.025], and postoperative VAS score 2 within 24 h (P = 0.031) compared with those in non-TXA group. In addition, the median hemoglobin count difference was significantly lower in TXA group than that of in non-TXA group (P = 0.045), while, the differences in median counts of red blood cell, hematocrit, and platelet between the two groups were comparable (all P > 0.05). Conclusion: Intra-articular injection of TXA might reduce the TBL and degree of postoperative pain within 24 h after shoulder arthroscopy.